9‐cis‐Retinoic acid induces a distinct regulatory dendritic cell phenotype that modulates murine delayed‐type allergy. (12th September 2017) - Kraus, Lea‐Franziska; Scheurmann, Natalie; Frenzel, Denis F.; Tasdogan, Alpaslan; Weiss, Johannes M.
Summary: Background: Hand eczema, which is frequently caused by delayed‐type allergy, is treated with 9‐ cis ‐retinoic acid (9cisRA). However, knowledge on how 9cisRA modulates skin immunity is sparse. Objective: As dendritic cells (DCs) are central in the pathogenesis of contact allergy, we investigated 9cisRA modulation of DC function in murine contact hypersensitivity (CHS). Methods: 9cisRA‐differentiated DCs (9cisRA‐DCs) were analysed for phenotype and function. In vivo 9cisRA‐DCs were tested in the CHS model. Results: 9cisRA induces the differentiation of a distinct CD103 − CD207 − regulatory DC phenotype. CD11c + DCs differentiated with 9cisRA have lower expression of major histocompatibility complex‐II and costimulatory molecules, but conversely have higher expression of the inhibitory coreceptor PD1‐L. 9cisRA‐DC culture does not induce the expression of proinflammatory cytokines, but strongly enhances osteopontin (OPN) secretion. 9cisRA‐DCs are compromised in the induction of T cell proliferation in vitro, but efficiently convert naive T cells into regulatory T cells (Tregs). Notably, OPN‐deficient 9cisRA‐DCs show a loss of Treg‐inducing function, which is re‐established by substituting OPN. In vivo, in allergic mice, allergen‐primed 9cisRA‐DCs suppress allergic inflammation and induce Treg accumulation in skin draining lymph nodes. Conclusions: This study describes 9cisRA‐mediated differentiation of a distinct DC phenotype that relies on OPN for Treg transformation and suppresses established CHS through Treg induction.